Hephaestin and Ceruloplasmin Play Distinct but Interrelated Roles in Iron Homeostasis in Mouse Brain. Issue 5 (18th March 2015) - Jiang, Ruiwei; Hua, Chao; Wan, Yike; Jiang, Bo; Hu, Huiyin; Zheng, Jiashuo; Fuqua, Brie K; Dunaief, Joshua L; Anderson, Gregory J; David, Samuel; Vulpe, Chris D; Chen, Huijun
Abstract: Background: Iron accumulation in the central nervous system (CNS) is a common feature of many neurodegenerative diseases. Multicopper ferroxidases (MCFs) play an important role in cellular iron metabolism. However, the role of MCFs in the CNS in health and disease remains poorly characterized. Objective: The aim was to study the role of hephaestin (HEPH) and ceruloplasmin (CP) in CNS iron metabolism and homeostasis. Methods: Iron concentrations and L-ferritin protein levels of selected brain regions were determined in global hephaestin knockout ( Heph KO), global ceruloplasmin knockout ( Cp KO), and wild-type (WT) male mice at 6–7 mo of age. Gene expression of divalent metal transporter 1 ( Dmt1 ), ferroportin 1 ( Fpn1 ), Heph, Cp, and transferrin receptor 1 ( Tfrc ) and HEPH protein level was quantitated in the same brain regions. Results: Iron and L-ferritin protein levels were significantly increased in Heph KO mouse brain cortex (iron: 30%, P < 0.05; L-ferritin: 200%, P < 0.05), hippocampus (iron: 80%, P < 0.05; L-ferritin: 300%, P < 0.05), brainstem (iron: 20%, P < 0.05; L-ferritin: 150%, P < 0.05), and cerebellum (iron: 20%, P < 0.05; L-ferritin: 100%, P < 0.05) regions than in WT and Cp KO mouse brain regions at 6 mo of age. Expression of the Heph gene was significantly increased in the Cp KO mouse cortex (100%; P < 0.01), hippocampus (350%; P < 0.001), brainstem (30%; P < 0.01), and cerebellum (150%; P < 0.001) than in WT controls, and Cp gene expression was significantly decreased in the Heph KO mouse hippocampus (20%; P < 0.05) than in WT control mice at 6 mo of age. Conclusions: Ablation of HEPH or CP results in disordered brain iron homeostasis in mice. Heph KO may provide a novel model for neurodegenerative disorders.